Lung Ultrasound in COVID‐19 A Role Beyond the Acute Phase?. (8th August 2020) - Gaspardone, Carlo; Meloni, Carlo; Preda, Alberto; Romagnolo, Davide; Brugliera, Luigia; Castellazzi, Paola; Tettamanti, Andrea; Conte, Caterina; Secchi, Antonio; Maranta, Francesco; Iannaccone, Sandro; Cianflone, Domenico
Abstract : Objectives: Coronavirus disease 2019 (COVID‐19) is a viral illness caused by severe acute respiratory syndrome coronavirus 2. With the increasing number of improved and discharged patients with COVID‐19, the definition of an adequate follow‐up strategy is needed. The purpose of this study was to assess whether lung ultrasound (LUS) is an effective indicator of subclinical residual lung damage in patients with COVID‐19 who meet discharge criteria. Methods: We prospectively enrolled 70 consecutive patients with COVID‐19 who had a prolonged hospitalization with inpatient rehabilitation between April 6 and May 22, 2020. All of the patients underwent an LUS evaluation at discharge. Data of patients with more severe disease during the acute phase (ie, required ventilatory support) were compared to those of patients with milder disease. Results: Among the 70 patients with COVID‐19 (22 women and 48 men; mean age ± SD, 68 ± 13 years), the LUS score before discharge was still frankly pathologic and higher in patients who had more severe disease during the acute phase compared to patients with milder disease (median [interquartile range], 8.0 [5.5–13.5] versus 2.0 [1.0–7.0]; P  < .001), even when both categories met internationally defined discharge criteria. Conclusions: Lung ultrasound can identify the persistence of subclinical residual lung damage in patients with severe COVID‐19 even if they meet discharge criteria. Considering the low cost, easy application, and lack of radiation exposure, LUS seems the ideal tool to be adopted in outpatient and primary care settings for the follow‐up of patients with COVID‐19.